Mobile System Application for Tourist Guide in Surabaya - D P Hapsari; W M Rahmawati; D H Sulaksono (IPTEK Journal of Proceedings Series, 2018)
Surabaya as the second largest city in Indonesia has been nominated as 12 cities with MICE (Meeting, Incentive, Conference, Exhibition) development. This causes the government of Surabaya concerns about the development of tourism such as history, education and maritime tourism. The biggest revenue of government came from trading sector, hotel, restaurant, and transportation. One of important things on developing tourism sector is the ease to access information of the tourism site. The infrastructure already completed by internet access as a smart city. All needs can be found online to save money. The implementation can be found in many fields, such as education, administrations, and tourism as the implementation of internet of thing. This research’s goal is to design mobile system based on android smartphone for Surabaya tour guide. The system provides GPS technic to give tourism information and to manage tourism site effectively. This system gives recommendation of the MICE place which is suitable for the user based on their requirement. TOPSIS algorithm will be used to rank the recommendation.